Statistical analysis on the impact of process parameters on tool damage during press hardening. (August 2016) - Schrenk, Mario; Krenn, Stefan; Rodríguez Ripoll, Manel; Nevosad, Andreas; Paar, Stefan; Grundtner, Reinhard; Rohm, Gregor; Franek, Friedrich
Highlights: We study the complex interdependence of processes parameters during press hardening. A novel test-rig is able to reproduce complex in-plant conditions in laboratory. The results allow optimising the process in terms of energy and tool wear reduction. Abstract: Automotive parts made of ultra-high strength steels are produced by press hardening in order to obtain high-strength components. During this process, formed parts are pressed against tools at high temperature, which ultimately yields to tool damage. Tool damage is especially detrimental since it not only affects the quality of the parts but also causes higher material consumption and reduces maintenance intervals. The extent of tool damage is determined by the process parameters but their influence is not yet clearly understood. The aim of this work is to investigate the influence of input process parameters on tool wear and maximum drawing force. To this end, a novel test rig is designed in order to reproduce typical press hardening conditions under well-controlled laboratory conditions. This set up is used to modify selected input parameters according to a Design of Experiments in order to investigate their impact on tool wear and drawing force. The results obtained can be summarised into two simple equations, which depend only on the most dominant parameters. This method allows a quantitative optimisation of the press hardening process, as illustrated by a practical example.